Psychological Resilience and Its relationship to Aggressive Behavior among Fencers - Abdul Hussein, Abbas Zaki; Hashim Ashour, Aya; Tawfiq Talib, Leila (مجلة دراسات وبحوث التربية الرياضية, 2023)
The research includes an introduction and emphasizes the importance of understanding and improving athletes' experience in sports as one of the main objectives. Despite the importance of physical, skill-related, and tactical aspects of the game, as well as enhancing players' performance during competitions, there are certain psychological characteristics expected to significantly impact players' performance levels in achieving better results. "Experienced athletes usually have the ability to control their physical energies and, at the same time, improve the direction of this energy." The research aims to identify the psychological readiness and aggressive behavior of the fencing national team players, as well as to determine the degree of relationship between psychological readiness and aggressive behavior among the fencing national team players. Regarding the research methodology, the researchers employed a descriptive approach using the survey method. The research population and sample consisted of 23 fencing players from the southern provinces, and the research instruments were applied to a sample of five players from the research population. The sample underwent psychological tests.